PENGARUH TERAPI MUROTTAL TERHADAP TINGKAT KONSENTRASI SISWA KELAS VIII. G DI MTSN 2 MUARA ENIM TAHUN 2018 - Shinta Maharani; Devy Dwi Putri (STIK SITI KHADIJAH PALEMBANG, 2019)
One of the tasks of the development of children aged 11-15 years is to think in a more abstract and logical way and more idealistic thinking. This ability to think will be disrupted if teenagers have difficulty concentrating during learning. Therefore we need a method that is fun and can make children relax in learning so that they can concentrate their concentration on ongoing learning. One method that can be used is the Murrotal Al-Qur'an therapy. The aim of the study was to determine whether there was any effect of murottal therapy on the concentration of students at Muara Enim 2 MTsN. This study used a quasi-experimental design with the design of the one group pretest posttest. The sample used was all students of class VIII.G at MTsN 2 Muara Enim. The results showed that the average concentration score of class VIII.G students before Murottal therapy was given was 10.84 with a standard deviation of 3.043. While the average concentration score of class VIII.G students after being given murottal therapy was 17.90 with a standard deviation of 1.233, so that the difference in mean concentration scores before and after murottal therapy was 7.06 with a standard deviation of 1.81. Wilcoxon signed ranks test obtained ρ value = 0,000, with a value of α = 0.05 (p <0.05), this shows that there is a significant difference between the concentration of students before and after being given murottal therapy. It is expected that the school can make a policy about the application of murottal therapy in increasing student concentration.